STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA (SDM) TENAGA PENDIDIK DI MTS. ANNIDA AL ISLAMY BEKASI TIMUR - Nurul Fadllillah; Irnie Victorynie (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
Education is the main basis for building quality human resources, and quality education will give birth to a superior generation, so the key is that competent educators are needed. This research aims to determine the strategies implemented in developing human resources for teaching staff at MTs Annida Al Islamy East Bekasi, which includes developing teachers' pedagogical, personality, social and professional competencies in improving the quality of education at MTs Annida Al Islamy East Bekasi. The method used in this research is a qualitative approach with data collection techniques through observation, informant interviews and documentation studies. The results of the research show that the human resource development strategy for teaching staff includes aspects of developing teacher pedagogical, personality, social and professional competence through (1) training and workshops, (2) mentoring and spiritual guidance activities, (3) social activities with students and parents, and all school members (4) curriculum development training, subject teacher discussion forums (MGMP), continuous professional training (PKB), educational technology workshops, direction, motivation and appreciation for outstanding teachers, provision of comprehensive scholarships to children of educators studying at MTs. Annida Al Islamy East Bekasi. The impact is to produce students who excel, are intelligent, have noble character and become superior madrasas. One of the constraining factors in developing human resources (HR) for teaching staff at MTs Annida Al Islamy, East Bekasi is the existence of senior teachers who do not understand information technology (IT), so they need intensive coaching and motivation to continually make themselves better at adapting. with the challenges of the times to realize educational ideals.